2021
DOI: 10.3389/fimmu.2021.656242
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Curcumin Blunts IL-6 Dependent Endothelial‐to‐Mesenchymal Transition to Alleviate Renal Allograft Fibrosis Through Autophagy Activation

Abstract: Fibrosis contributes to graft loss in chronic renal allograft injury. Endothelial‐to‐mesenchymal transition (EndMT) plays an important role in the development of fibrosis following kidney transplantation. Autophagy plays an important role in the homeostasis of diverse cell types including endothelial cells. Here we demonstrate that inhibition of autophagy by treatment with 3-methyladenine (3-MA) or by silencing autophagy-related (ATG)5 promoted interleukin (IL)-6–dependent EndMT in human umbilical vein endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It was found that mitochondrial dysfunction was significantly improved in renal interstitial cells of UUO rats after curcumin treatment, which in turn inhibited the activation of NLRP3 inflammasome and the expression of PI3K/AKT/mTOR signaling pathway, alleviating the progression of renal fibrosis by reducing the inflammatory response and regulating autophagy [ 42 ]. Curcumin can also attenuate EndMT and fibrosis occurring after kidney transplantation, which is similarly accomplished by activating cellular autophagy [ 43 ]. In addition, curcumin can act as an anti-oxidant that can alleviate renal fibrosis induced by scavenging excess ROS, inhibiting the activity of NADPH oxidase, improving mitochondrial redox balance [ 44 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…It was found that mitochondrial dysfunction was significantly improved in renal interstitial cells of UUO rats after curcumin treatment, which in turn inhibited the activation of NLRP3 inflammasome and the expression of PI3K/AKT/mTOR signaling pathway, alleviating the progression of renal fibrosis by reducing the inflammatory response and regulating autophagy [ 42 ]. Curcumin can also attenuate EndMT and fibrosis occurring after kidney transplantation, which is similarly accomplished by activating cellular autophagy [ 43 ]. In addition, curcumin can act as an anti-oxidant that can alleviate renal fibrosis induced by scavenging excess ROS, inhibiting the activity of NADPH oxidase, improving mitochondrial redox balance [ 44 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…Moreover, autophagy is reported to increase in the mice colitis model, which helps to ease inflammation (3). In another study, the antifibrotic effects of curcumin were demonstrated via its alleviation of IL-6-induced endothelial-to-mesenchymal transition through promoting autophagy in allografted organs and human umbilical vein endothelial cells (HUVECs) (117). However, it is reported that autophagy in immune cells could induce an immune response that finally aggravates fibrosis.…”
Section: Autophagy and Intestinal Fibrosismentioning
confidence: 99%
“…Using curcumin, a known p300 inhibitor, in vitro and in vivo , Antoinette et al ( 58 ) found that inhibition of p300 activity can reduce Smad acetylation and TGF-β activity, and reduce cardiac hypertrophy, improve diastolic function, and reduce extracellular matrix production, but not affect blood sugar. Similarly, curcumin has been shown to inhibit IL-6-dependent EndMT and attenuate renal transplant fibrosis through autophagy activation ( 59 ).…”
Section: Histone Acetyltransferase P300 Regulate Endothelial- Mesench...mentioning
confidence: 99%